2017
DOI: 10.1038/gim.2016.141
|View full text |Cite
|
Sign up to set email alerts
|

Prescription medication changes following direct-to-consumer personal genomic testing: findings from the Impact of Personal Genomics (PGen) Study

Abstract: Purpose To measure the frequency of prescription medication changes following direct-to-consumer personal genomic testing (DTC-PGT) and their association with the pharmacogenomic results received. Methods New DTC-PGT customers were enrolled in 2012 and completed surveys prior to return of results and 6 months post-results; DTC-PGT results were linked to survey data. ‘Atypical response’ pharmacogenomic results were defined as those indicating an increase or decrease in risk of an adverse drug event or likelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 19 publications
0
32
2
Order By: Relevance
“…In this sense, one could strongly argue that future examinations of pharmacogenomic implementation—including perhaps pragmatic clinical trials—might not only need to measure patient outcome benefits for individual drug-gene pairs, but also should consider physician utilization as a potential indicatory benchmark of utility. The role of the patient in potentially influencing physician prescribing behavior must also be considered(35). …”
Section: Discussionmentioning
confidence: 99%
“…In this sense, one could strongly argue that future examinations of pharmacogenomic implementation—including perhaps pragmatic clinical trials—might not only need to measure patient outcome benefits for individual drug-gene pairs, but also should consider physician utilization as a potential indicatory benchmark of utility. The role of the patient in potentially influencing physician prescribing behavior must also be considered(35). …”
Section: Discussionmentioning
confidence: 99%
“…Through review of the scientific and gray literature, 12 companies were identified that previously offered direct-to-consumer pharmacogenomic testing. 5 , 6 , 9 However, only one – 23andMe ( Table 1 ) – currently offers direct-to-consumer testing. Of the remaining 11, 7 of the companies no longer offer testing.…”
Section: Available Direct-to-consumer Pharmacogenomic Testsmentioning
confidence: 99%
“…Results from the Impact of Personal Genomics (PGen) Study, which recruited patients who had received direct-to-consumer testing through 23andMe or Pathway Genomics, showed that 91% of patients received an atypical drug metabolism result and 20% of patients discussed their genetic results with their primary care provider. 9 , 10 However, direct-to-consumer testing has been marred with controversy. Concerns of test validity and quality, misinterpretation of results, and the potential for inappropriate medical decisions and health care services dampened enthusiasm.…”
Section: Fda Involvement In Direct-to-consumer Pharmacogenomic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we report here on only a subset of the measures administered in the larger PGen Study, as summarized in Table 1 . The reader is referred to our previously published work for findings on other study outcomes including comprehension of test results [14] , changes in disease risk perceptions [17] , changes in prescription medication use [18] , and use of primary care services following testing [19] .…”
Section: Overviewmentioning
confidence: 99%